Overview of the Sciomyzidae (Diptera: Sciomyzoidea) of the Americas south of the United States - Murphy, William L.; Abercrombie, Jay; González, Christian R.; Knutson, Lloyd (Zootaxa, 2023)
Treated herein are the 113 described species and two described subspecies in 25 genera of the family Sciomyzidae (snail-killing or marsh flies) known from the Americas south of the United States. Included are details on type specimens, references to generic transfers and synonymies, taxonomy, biology, gastropod hosts/prey, immature stages, chromosomes, biological and phenological groups, general distribution, and molecular data. Annotated keys are presented to adults of genera known from the Nearctic-Neotropical interface area and the Neotropics as well as the first key to all sciomyzid genera known from the Nearctic Region. Also presented is the first key to third-instar sciomyzid larvae in the Neotropical Region. Sepedonea isthmi (Steyskal) is placed as a junior synonym of S. annulata Macquart (new status), and Tetanocera plumifera Wulp is placed as a junior synonym of T. plumosa Loew (new status).